Approximation of the Classes H_p^Ω of Periodic Functions of Many Variables in the Space L_p - Derev’yanko, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We establish upper estimates for the approximation of the classes H_p^Ω of periodic functions of many variables by polynomials constructed by using the system obtained as the tensor product of the systems of functions of one variable. These results are then used to establish the exact-order estimates of the orthoprojective widths for the classes H_p^Ω in the space L_p with p ∈ {1, ∞}.